Building Indonesian Humanity through Civic Education in High School - Hijriana Hijriana (Newinera Publisher, 2020)
This article provides an explanation of the concept of Building a Whole Indonesian Man in Pancasila Education. Developing Indonesian people as a whole is, in essence, Indonesia's national development. It is also the basic concept of Indonesian education. Building a Whole Indonesian Man has a relationship with Pancasila. As discussed earlier that Pancasila is the basis of the state which is the guideline for the Indonesian nation. So whatever is to be done within the Indonesian state basically must make Pancasila as a guideline in regulating the life and welfare of its people.